(untitled) (Uzbek Scholar Journal, 2023)
It is no exaggeration to say that the scientific method is an integral part of linguistics and methodology. This article provides information about the scientific method, scientific term, scientific texts, and first of all, the history of the scientific method, stylistics, and speech methodology, and its departments. Examples are always given to it.